2016
DOI: 10.1016/j.jnutbio.2015.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Isocaloric manipulation of macronutrients within a high-carbohydrate/moderate-fat diet induces unique effects on hepatic lipogenesis, steatosis and liver injury

Abstract: Diets containing excess carbohydrate and fat promote hepatic steatosis and steatohepatitis in mice. Little is known, however, about the impact of specific carbohydrate-fat combinations on liver outcome. This study was designed to determine whether high-energy diets with identical caloric density but different carbohydrate and fat composition have unique effects on the liver. Four experimental diets were formulated with 60% kcal carbohydrate and 20% kcal fat, each in nearly pure form from a single source: starc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…This is in line with other mouse studies where high‐fat diet stimulated hepatic de novo lipogenesis and this effect was stronger with longer time spent on high‐fat diet (Pierce et al. ). In human studies, the relation between age and hepatic de novo lipogenesis has received little attention to date, with one study reporting increased hepatic de novo lipogenesis in elderly compared to younger controls (Flannery et al.…”
Section: Discussionsupporting
confidence: 92%
“…This is in line with other mouse studies where high‐fat diet stimulated hepatic de novo lipogenesis and this effect was stronger with longer time spent on high‐fat diet (Pierce et al. ). In human studies, the relation between age and hepatic de novo lipogenesis has received little attention to date, with one study reporting increased hepatic de novo lipogenesis in elderly compared to younger controls (Flannery et al.…”
Section: Discussionsupporting
confidence: 92%
“…The link between the low‐fat diet and de novo lipogenesis rests in the fact that this diet has a relatively high‐carbohydrate content compared to the high‐fat diet. Indeed, others have shown that a high‐carbohydrate diet will produce greater steatosis than a high‐fat diet, with corresponding markers of increased hepatic de novo lipogenesis (Li et al., ; Pierce et al., ; Schwarz et al., ). Thus, in our model, we propose that increased carbohydrate flux into the liver serves as a substrate for de novo lipogenesis, with the resultant fatty acids channeled toward TG synthesis catalyzed by DGAT2.…”
Section: Discussionmentioning
confidence: 99%
“…Follow‐up studies using both high‐ and low‐fat liquid diets led us to focus on potential mechanistic differences in the induction of alcoholic steatosis in mice consuming alcohol as part of diets with different fat content. While it is known that diets with different macronutrient composition can contribute differently to nonalcoholic fatty liver disease (NAFLD; Li et al., ; Pierce et al., ), to our knowledge this has not been previously explored at the molecular level in the context of liquid diet consumption and alcoholic hepatic steatosis.…”
mentioning
confidence: 99%
“…Scraped TG bands were hydrolyzed and FA methyl esters were formed by incubating in 3 N HCl in methanol (MilliporeSigma) at 65°C for 1 hours. FA methyl esters were extracted and derivatives were analyzed for deuterium enrichment by gas chromatography/mass spectrometry as described previously (53,54).…”
Section: Methodsmentioning
confidence: 99%